WHAT MAKES A CUSTOMER WANT TO USE THE ISLAMIC PAWN BROKING (AR-RAHNU) SCHEME? A CASE STUDY OF LOW-INCOME CIVIL SERVANTS IN WISMA PERSEKUTUAN KOTA BHARU, KELANTAN - Abdullah Thani , Ayu Kamareenna; Rosely, Nurhidayah; Amran, Atiela; Nik Min , Nik Mohd Faris; Azhari, Nurul Nadhira Amalin (Journal of Islamic, Social, Economics and Development, 2024)
Islamic pawn broking, also known as ArRahnu, is regarded as a rapid and efficient financial business. In Islam, the contract is considered a philanthropic and voluntary agreement (tabarru‟). From an Islamic standpoint, conventional pawnbroking functions in a manner that is contrary to the following perspective. It offers financial services by accepting a customer's assets as collateral and charging interest on the money lent. In contrast, ArRahnu service is founded on three principles: Qardhul Hassan, Wadiah, and Ujrah. The Wadiah concept is classified into two types: Yad Amanah and YadDhamanah. This paper aims to ascertain the customer's intention to use the ArRahnu service by examining five dimensions: attitude, social impact, religious obligation, pricing structure, and intention to use. The objective of this paper is to analyze the variations in the intention to use Islamic pawnbroking (ArRahnu) based on demographic factors such as gender, age, educational level, and monthly income level. Additionally, it aims to establish the correlation between attitude, social influence, religious obligation, and pricing system with the intention to use Islamic pawn broking (ArRahnu). Lastly, it seeks to investigate the primary factors that predominantly influence the intention to use Islamic pawn broking (ArRahnu). The study has been focused on a particular group of individuals, namely low- income government employees residing in Wisma Persekutuan, Kota Bharu, Kelantan. The study utilized a quantitative research methodology, employing a questionnaire as the data collection instrument. The sample size consisted of 242 respondents. The data resulted in a response rate of approximately 85 percent. The findings of this study indicate that customers mostly utilize the ArRahnu service due to two main factors: social influence and religious obligation. Consequently, this study has made significant contributions and recommendations to both the government and financial organizations about the enhancement of Ar-Rahnu utilization.